Analisis Pemasaran Cabai Rawit Di Desa Tutuling Jaya Kecamatan Wasile Kabupaten Halmahera Timur - Banelamo, Rolief; Pangemanan, Paulus Adrian; Waney, Nordy Fitsgerald Lucky (Sam Ratulangi University, 2023)
This study aims to describe marketing channels, calculate marketing margins and marketing efficiency of cayenne pepper in Tutuling Jaya Village, Wasile District. Data collection used a survey method with snowball sampling. The total sample size was 12 respondents, consisting of 4 respondents as a farmer sample, 1 collector trader sample, 2 wholesalers sample, 5 respondents as a retailer sample. The result of the research is that the marketing of cayenne pepper in Tutuling Jaya Village has 2 marketing channels. Marketing channel-1 consists of: farmers - collectors - consumers. Channel-1 marketing margin is IDR5.000/kg consisting of: marketing costs IDR3,910/kg, a profit of IDR1,090/kg. Marketing channel-2 consists of: farmers - collectors - wholesalers - retailers - consumers. The marketing margin for cayenne pepper marketing channel-2 is IDR45,000/kg, consisting of: marketing costs IDR18,965/kg, and profits of IDR26,036/kg. Marketing of cayenne pepper in Tutuling Jaya Village, Wasile District, East Halmahera Regency on marketing channel-1 was more efficient than marketing channel-2. The proportion of marketing costs to the price paid by the final consumer is relatively smaller, namely only 9.78 percent in marketing channel-1 compared to marketing channel-2 which is 23.70 percent.